(3GdGKfG YTQjI aj GdWgGQIs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO MeO Gddg Ydi BdGFg (B... (3gPg QSGdI GKfi YTQjI JJdh Ydjc eSGFd GdWgGQI Ydi fgL LOjO hfeW SOjO (B... (3aGbhd Ef GdeWGdH GdeJYdbI HGdWgGQI GKfG YTQ eWdHG GdChd eG GdWgGQI GdKGfj ce GdWgGQIs
(3BNQgG (B:s
(3BNQgG(B: (3hGWGdI GdecK HZjQ MGLI hGONGd GdNdGA TjFG Ydjg GSe Gddg JYGdi Ch CMO GdeYUhejf SdGe Gddg Ydjge(B. (3JeJ GdWgGQjI GdGKfi YTQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis